2016
DOI: 10.1016/j.renene.2015.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis on solar thermal systems: A better understanding of their sustainability

Abstract: a b s t r a c tThis paper presents a review of exergy analysis of solar thermal systems. It includes both various types of solar collectors and various applications of solar thermal systems. As solar collectors are an important technology when sustainability is considered, exergy analysis, which gives a more representative performance evaluation, is a valuable method to evaluate and compare possible configurations of these systems. It should be noted that this review is based on literature published in the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(34 citation statements)
references
References 55 publications
(28 reference statements)
0
34
0
Order By: Relevance
“…As far as the authors are aware there have been few, if any, in depth research on exergy analysis of evacuated tube collectors and most of the previous works focused on flat plate collectors [12,13], solar air collector [14], and all glass evacuated solar collector [15]. As mentioned by Kalogirou, et al [16] evacuated tube solar collectors treated less often from an exergy view point. Due to lack of sufficient research, using exergy and 2 nd law concept in thermal analysis of heat pipe evacuated collectors, a comprehensive model for these collectors is presented in this work.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the authors are aware there have been few, if any, in depth research on exergy analysis of evacuated tube collectors and most of the previous works focused on flat plate collectors [12,13], solar air collector [14], and all glass evacuated solar collector [15]. As mentioned by Kalogirou, et al [16] evacuated tube solar collectors treated less often from an exergy view point. Due to lack of sufficient research, using exergy and 2 nd law concept in thermal analysis of heat pipe evacuated collectors, a comprehensive model for these collectors is presented in this work.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical analysis was performed to investigate the exergetic efficiency of single pass SAHs with fins and baffles by Sabzpooshani et al, 16 and it was concluded that the exergetic efficiency was directly proportional to the air flow rate and the irradiance intensity. Review papers of numerical and experimental studies of the energy and exergy efficiencies of SAHs have been presented by Oztop et al, 17 Kalogirou et al, 18 and Sansaniwal et al 19 The thermal performance of different SAH systems was investigated in term of the first and second laws of thermodynamics by Bahrehmand and Ameri, 20 and they reported that the absorber plate temperature for a double glass cover was greater than that of an absorber plate with a single glass cover. An experimental test was carried out by Edalatpour et al 21 to evaluate the energetic and exergetic performance of an SAH with a double glass cover.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a reference book deals essentially with the handling of the solar intensity fluctuations on an automatism point of view, on the basis of constant output temperature for the control of large‐scale steam turbines, with or without thermal storage. Since then, it has been shown, by the use of exergy approach that constant output temperature is not optimal, either for steam plants or other plants . The latest references present exergy optimizations of solar plants based on the available exergy flow only.…”
Section: Introductionmentioning
confidence: 99%